Analisis Disiplin Kerja Pegawai Dewan Perwakilan Rakyat Daerah Kabupaten Malang - Moch Agung Kurniawan; Yoga Aldi Kurniawan; Niki Puspita Sari (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the factors that influence the work discipline of employees of the Regional People's Representative Council (DPRD) of Malang Regency during operational hours. Work discipline, which includes compliance with regulations, effective use of time, responsibility, and absence rate, is a key element in improving organizational performance and efficiency. A qualitative approach was used with data collection techniques through observation, interviews, and document studies. The results of the study showed that the majority of employees comply with the regulations, but there were several cases of non-compliance and ineffective use of time. In addition, employee responsibility is generally high, although there are still obstacles in completing tasks on time. A good absence rate is an indicator of discipline, but some employees show a high level of absenteeism. The implications of this study include strategic recommendations such as strengthening work rules, time management training, and the use of digital absence technology to improve employee discipline. These findings are expected to help improve overall organizational performance.